Coastal vulnerability assessment using electrical resistivity tomography in Padang Betuah, Central Bengkulu - Suhendra, Suhendra; Halauddin, Halauddin; Lizalidiawati, Lizalidiawati; Sinaga, Jesika Erni Elfrita; Fadli, Darmawan Ikhlas; Idris, Beni Syakban (Institute of Advanced Engineering and Science, 2023)
Abrasion disaster in the coastal area of Padang Betuah Beach has a high level of abrasion in Central Bengkulu. The local community utilizes abrasion in the coastal area as a tourist attraction and becomes local revenue in the research location. The location that becomes a tourist attraction is decreasing because the coastal area’s land has been abraded. After conducting research using the electrical resistivity tomography (ERT) method in 2D and 3D, it was found that claystone dominated the coastal area at the research location with a resistivity value of 16-200 Ωm at a depth of 15-20 m. The coastal area in Padang Betuah Beach is composed of clay shale rocks (207-220 Ωm), and the depth is 2-14.8 m. Clay shale rocks are not abraded in stones with resistivity values >250 Ωm. This is caused by clay shale, which has low porosity, so it has a compact rock density. Seawater is identified at a depth of 21-63 m with a resistivity value of 2.225-10.2 Ωm. The depth of seawater determined follows the average height of the cliffs in the research location. The abrasion process can be slowed down by making jetties, water breakers, and mangrove cultivation.